Atypical Presentation of Thrombocytopenia in Malaria- A Case Report - Saketh Ramineni; Padma; Sathyapriya; Shiny Thomson; Meera (Journal of Coastal Life Medicine, 2022)
Malaria is a common infection in India caused by plasmodium, it is transmitted by female anopheles mosquito. In some percentage of patients there is a decrease in platelet counts in acute malaria. There has been reports of some minor bleeding manifestations in people with malaria. Here we present a case of severe thrombocytopenia in Vivax malaria.